Effective Use of Non-Reliance Clauses: Satisfying Lowe v Lombank - LOW, Kee Yang (Institutional Knowledge at Singapore Management University, 2009)
The inclusion in contracts of “non-reliance” clauses, as a means of pre-empting assertions of misrepresentation, has become commonplace. The validity and effectiveness of such clauses is another matter. This article discusses how a non-reliance clause may act as an evidential estoppel.